Simultaneous spontaneous dissection of right carotid and left vertebral artery followed by spontaneous coronary artery dissection in a patient with renal fibromuscular dysplasia and aneurysm - Kobierska, Agata; Zalewska, Joanna; Michałowska, Ilona; Dziewierz, Artur; Kądziela, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
Spontaneous coronary artery dissection (SCAD) is an increasingly recognized, non-iatrogenic, non-traumatic, non-atherosclerotic disease presenting as an acute coronary syndrome [1, 2]. The dissection can recur and involve not only coronary but also visceral, cerebral and cervical arteries [3]. The predictors for recurrence remain unspecified. However, one study suggested fibromuscular dysplasia (FMD) and migraine as potential risk factors [4].